Structural evidence for native state stabilization of a conformationally labile amyloidogenic transthyretin variant by fibrillogenesis inhibitors. Issue 15 (20th June 2013) - Zanotti, Giuseppe; Cendron, Laura; Folli, Claudia; Florio, Paola; Imbimbo, Bruno Pietro; Berni, Rodolfo
Abstract : TTR andTTR bind byx‐ray crystallography (View interaction ) Abstract : An acidic pH‐induced large conformational change affects the amyloidogenic I84S TTR. CHF5074 and diflunisal bind to T4 sites of TTR, inhibiting fibrillogenesis. The binding of fibrillogenesis inhibitors prevents structural alterations of I84S TTR. Long‐range stabilizing effects occur upon binding of ligands to T4 sites of I84S TTR. TTR ligands appear to preserve the TTR native state by rigidifying the whole tetramer.